An investigation of the ballistic performance of independent ceramic target. (September 2020) - Khan, M.K.; Iqbal, M.A.; Bratov, V.; Morozov, N.F.; Gupta, N.K.
Abstract: The ballistic experiments have been carried out on alumina 99.5% bare ceramic plates for studying the initiation and propagation of brittle fracture and the resistance offered by the target. The ceramic tiles of size, 100 mm × 100 mm, and thickness, 5 mm, were impacted by the ogival nosed hardened steel 4340 projectiles of diameter 10.9 mm and mass 30 grams at velocities in the range 52–275 m/s. The ceramic fragments were carefully collected to examine the cracking patterns at the front and the back surfaces. The cracks developed in the target were studied extensively to develop more insight into the fracture mechanism. The energy absorbed by the target has been studied and correlated with respect to the fracture mechanism of the target. Numerical simulations have been performed on a commercial finite element code and the experimental findings have been reproduced in order to further understand the fracture and fragmentation behaviour and its influence thereon the ballistic characteristics of the target. The Johnson-Holmquist-2 (JH-2) constitutive model has been used for simulating the material behaviour of ceramic and the Johnson-Cook (JC) elasto-viscoplastic material model for simulating the behaviour of the steel projectile. The behaviour of ceramic target under oblique impact was explored numerically. The damage in the projectile was found to be higher in case of oblique impact. Both the experimental and numerical findings have described an increase in the crack density with the increase in the incidence velocity of the projectile. The average size of the fragments has also been found to be reduced with the increase in the projectile incidence velocity. Graphical abstract: Image 1 Highlights: Damage and fracture of Alumina 99.5% ceramic was studied under ballistic impact. Variation of fracture conoid angle has been observed under varying impact velocity. Numerical model correctly reproduced the residual velocities and damage. Higher damage in target and impactor was observed under oblique impact.